MODEL-MODEL PENGEMBANGAN WAYANG UNTUK GENERASI MUDA - S., Sunardi (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2016)
The less of the youth interest toward wayang is caused by the transmission system stagnancyof wayang and the decrease of commitment to make wayang closer to them. Besides, thetechnology progress and media publication bring the transparancy for the youth tofollow thetrend of instant arts outside their own culture. The effort to get their interest is bytrying to lovewayang progressively and simultaneously. Wayang development is based on theIndonesianvalues. It needs to design an alternative model of Indonesian wayangdevelopment as an effortto increase the youth interest toward wayang. Strategy of wayang developing is executed bydetermining the target; composing public segmentation; arranging model concept; buildingcooperation; designing the various model of wayang developing; socializing the model to thepublic; and keeping the continuity. The wayang developing is led to focus on the mannerseducation and the extension of the creative industry to sustain the nation building.Keywords: model of wayang developing, the youth, value, strategy, manners.